Creative Flexibility Performance Is Neither Related to Anxiety, Nor to Self-Control Strength, Nor to Their Interaction - Bertrams, Alex; Englert, Chris (Frontiers in Psychology, 2019)
Previous research has reliably found that self-control strength moderates the anxiety-performance relationship for cognitive and perceptual-motor tasks that involve executive functioning. In the present preregistered experiment (N = 200; https://aspredicted.org/a775h.pdf), we investigated whether the interaction of anxiety and self-control also predicts creative flexibility performance. According to the Attentional Control Theory, anxiety can impair executive functioning. In the case that creative flexibility relies on executive functions, anxiety should therefore interfere with creative flexibility performance. However, self-control strength has been demonstrated to serve as a buffer against the negative effects of anxiety on executive functioning. Therefore, we assumed that there will be a negative relationship between anxiety and creative flexibility performance, and that this negative relationship would be more pronounced for participants who are low compared to high in momentary self-control strength. Analogous to the previous studies, we manipulated the participants’ self-control strength (ego depletion vs. no depletion) and subsequently induced a potentially threatening test situation. The participants then completed a measure of their state anxiety and a standardized test of creative flexibility. Contrary to our expectation, self-control strength, state anxiety, and their interaction did not predict creative flexibility performance. Complementary Bayesian hypothesis testing revealed strong support for the null hypothesis. Therefore, we conclude that, at least under certain conditions, creative flexibility performance may be unrelated to resource-dependent executive functions.